MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DI SMP NEGERI 7 PADANG - Arman Arman (PAKAR Pendidikan, 2015)
The purpose of this class action research to find out the application of the method of learning Flashcard learning outcomes against grade VIII.I SMP Negeri Padang in 7 subjects, information and communication technology. Flashcard is one method of learning in the form of presentation of the learning material through the image. These image is a series of messages was presented with information on each painting that is written on the back. The research method used the class Act (Classroom Action Research) with the analysis of the percentage against the result of learning. This research was conducted as many as three cycle with many meetings each cycle is two times. The results showed that Flascard learning methods can increase the activity and results of student learning. The average student learning activities at each cycle.